Pendidikan Karakter Sebagai Upaya Penguatan Bullying Di SDN Palmerah 03 Pagi Jakarta Barat - Day Sitanggang, Realita; Sofyan, arlinda (Media Abdimas, 2024)
Abstract School is one of the many places where bullying or bullying problems occur. Palmerah 03 Pagi State Elementary School is one of the schools whose students are not immune to cases of bullying. The State Elementary School (SDN) period is the initial period for children to adapt to their surrounding environment, and during this State Elementary School period children still have a tendency to imitate things that happen around them. Therefore, the aim of this activity is to provide knowledge and character development for participants who are students at SDN Palmerah 03 Pagi and find a model for preventing bullying through character education and the role of the school. Character education is an important role in shaping children's morals. Through character education from an early age, it is hoped that we can produce a good, competent and dignified generation of the nation. The results of the activities that have been carried out are changes in awareness, knowledge and attitudes that show the prevention of bullying. Previously, many students still didn't know what bullying was. After being exposed to bullying and how to prevent it, students became more careful not to engage in bullying  ABSTRAK Sekolah merupakan satu diantara banyaknya tempat yang banyak terjadi masalah perundungan atau bullying. Sekolah Dasar Negeri Palmerah 03 Pagi merupakan salah satu sekolah yang siswanya tidak luput dari kasus bullying. Masa Sekolah Dasar Negeri (SDN) menjadi masa yang awal bagi anak untuk beradaptasi dengan lingkungan sekitar, dan pada masa Sekolah Dasar Negeri ini anak-anak masih memiliki kecenderungan meniru hal-hal yang terjadi di sekitarnya. Oleh karena itu, tujuan dari kegiatan ini adalah untuk memberikan pengetahuan serta pembinaan karakter bagi peserta yang merupakan siswa-siswi SDN Palmerah 03 Pagi dan menemukan model pencegahan bullying melalui pendidikan karakter dan peran sekolah. Pendidikan karakter merupakan peranan penting dalam membentuk moral anak. Melalui Pendidikan karaker sejak dini diharapkan dapat mencetak generasi bangsa yang baik, berkompeten,dan bermartabat. Hasil dari kegiatan yang sudah dilakukan adalah adanya perubahan kesadaran, pengetahuan dan sikap yang menunjukan pencegahan bullying. Dimana sebelumnya siswa masih banyak yang belum mengetahui apa itu bullying. Setelah dipaparkan mengenai bullying dan cara pencegahannya, para siswa menjadi lebih berhati hatiuntuk tidak melakukan bullying